Recyclable and Stable Strain Sensors Based on Semi‐Wrapped Structure of Silver Nanowires in Polyvinyl Alcohol for Human Motion Monitoring - Yiyi Chen; Yanlin Li; Qi Zhang; Ting Peng; Huangzhong Yu; Shengwei Shi (Macromolecular Materials and Engineering)
Abstract Highly sensitive strain sensors have been widely used in human motion monitoring, medical treatment, soft robots, and human–computer interaction, and the recycling of functional materials is in a huge demand for eco‐friendly and sustainable electronics. However, the manufacturing of recyclable strain sensors still remains challenging. Here, a semi‐wrapped structure based on silver nanowires and polyvinyl alcohol is proposed to realize a recyclable and stable strain sensor. It has shown excellent sensitivity, fast response, high stretchability and good environmental stability, and is successfully applied for human motion monitoring. In addition, a simple strategy is developed to effectively recycle silver nanowires in an eco‐friendly manner. The recyclable and stable strain sensor demonstrates potential applications in wearable and stretchable electronics, and the recycling strategy can be extended to other noble metal nanomaterials.